The computational complexity of three graph problems for instances with bounded minors of constraint matrices - Gribanov, D.V.; Malyshev, D.S. (Discrete Applied Mathematics, 2017)
We consider boolean linear programming formulations of the independent set, the vertex and the edge dominating set problems and prove their polynomial-time solvability for classes of graphs with (augmented) constraint matrices having bounded minors in the absolute value.